Determinants of inter-country internet diffusion rates - Phanindra V. Wunnava; Daniel B. Leiter (Institute for the Study of Labor (IZA), 2008)
This paper employs cross-sectional data from 100 countries to analyze the main determinants of inter-country Internet diffusion rates. We set up an empirical model based on strong theoretical foundations, in which we regress Internet usage on variables that capture social, economic and political differences between these countries. Our results support past findings that economic strength, infrastructure and knowledge of the English language positively affect Internet connectivity. In addition to these indicators, the openness of a country, tertiary enrollment, and income equality are found to also have a significant positive effect on Internet diffusion.
urn:nbn:de:101:1-2008090173
Keywords: O33; 330; Internet; technological diffusion; inequality; education; English proficiency; Internet; Medienverhalten; Innovationsdiffusion; Soziale Ungleichheit; Bildungsniveau; Englisch (Sprache); Welt